1997
DOI: 10.1053/jhep.1997.v26.pm0009303503
|View full text |Cite
|
Sign up to set email alerts
|

Partial cloning of rat CD34 cDNA and expression during stem cell- dependent liver regeneration in the adult rat

Abstract: adhesion and ''homing'' during the inflammatory process, The sialomucin CD34 is expressed on human and mouse and in stem/progenitor cell localization/adhesion in the bone hematopoietic stem cells and is used as an important marker marrow. 1 CD34 is not only expressed in hematopoietic stem/ for isolating the hematopoietic stem/progenitor cells. The progenitor cells, but also in small-vessel endothelial cells, involvement of hepatic stem cells in liver regeneration under and embryonic fibroblast. 1 Human, 3,4 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 2 publications
4
56
0
Order By: Relevance
“…As already discussed, we know that a number of surface determinants are shared between haematopoietic derived progenitor cells and oval cells, including c- kit ,26CD34,27 and Thy-128 in rodents, and c- kit 23 and CD3424in humans. These observations have been brought sharply into focus with the demonstration that a population of haematopoietic stem cells originating in the bone marrow may give rise to oval cells in the liver and have the potential to further differentiate into hepatocytes and/or ductal cells 29.…”
Section: Haematopoiesis and Liver Stem Cellsmentioning
confidence: 82%
“…As already discussed, we know that a number of surface determinants are shared between haematopoietic derived progenitor cells and oval cells, including c- kit ,26CD34,27 and Thy-128 in rodents, and c- kit 23 and CD3424in humans. These observations have been brought sharply into focus with the demonstration that a population of haematopoietic stem cells originating in the bone marrow may give rise to oval cells in the liver and have the potential to further differentiate into hepatocytes and/or ductal cells 29.…”
Section: Haematopoiesis and Liver Stem Cellsmentioning
confidence: 82%
“…Those cells can generate both hepatocytes and biliary duct cells 5 . A number of studies reveal that oval cells express hematopoietic markers, such as c‐kit, 6 Thy‐1, 7 and CD34 8 . In addition, they also express the hepatocyte‐specific marker alpha‐fetoprotein (AFP), the liver epithelial cell markers (cytokeratin [CK]8 and CK18), the biliary‐specific markers (CK7 and CK19), and the oval cell‐specific marker (OV6) in the rodent liver 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…messenger RNA (mRNA) was reverse transcribed and complementary DNA (cDNA) underwent 40 rounds of amplification (ABI‐Prism 7700; PerkinElmer/Applied Biosystems, Foster City, CA) as follows: 40 cycles of a 2‐step PCR (95°C for 15 seconds, 60°C for 60 seconds) after initial denaturation (95°C for 10 minutes) with 2 μL of DNA solution, 1× TaqMan SYBR Green Universal Mix PCR reaction buffer (Applied Biosystems). Primers used for amplification were obtained from various references 13, 14, 28–31. mRNA levels were normalized using GAPDH as housekeeping gene and compared with mRNA levels in fresh rat liver cells, rat BM, whole pancreas, pyloric stomach, and duodenum.…”
Section: Methodsmentioning
confidence: 99%
“…Oval cells are bipotential and give rise to both hepatocytes and biliary ductal cells 9, 10. Recent studies have identified many cell‐surface markers for oval cells both in rodents and humans, including the hematopoietic markers Thy1.1, cluster domain (CD)34, Flt3‐receptor, and c‐kit 11–14. Oval cells also express alpha‐fetoprotein (AFP), cytokeratin (CK)19, and γ‐glutamyl‐transferase and stain positive with the monoclonal antibodies; OC.2, OV‐6, and BD1 15.…”
mentioning
confidence: 99%